2006
DOI: 10.1038/sj.npp.1301225
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study on Sustained Effects of Low-Dose Ecstasy Use on the Brain in New Ecstasy Users

Abstract: It is debated whether ecstasy use has neurotoxic effects on the human brain and what the effects are of a low dose of ecstasy use. We prospectively studied sustained effects (42 weeks abstinence) of a low dose of ecstasy on the brain in ecstasy-naive volunteers using a combination of advanced MR techniques and self-report questionnaires on psychopathology as part of the NeXT (Netherlands XTC Toxicity) study. Outcomes of proton magnetic resonance spectroscopy ( 1 H-MRS), diffusion tensor imaging (DTI), perfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 99 publications
(112 reference statements)
1
29
0
1
Order By: Relevance
“…Our findings are consistent with two small scale longitudinal studies ([de Win et al, 2006] and [de Win et al, 2007]), where no association was found between common mental health disorders and later ecstasy use. There is a range of reasons why our results might differ from those of others.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with two small scale longitudinal studies ([de Win et al, 2006] and [de Win et al, 2007]), where no association was found between common mental health disorders and later ecstasy use. There is a range of reasons why our results might differ from those of others.…”
Section: Discussionsupporting
confidence: 92%
“…The few longitudinal studies that have assessed the nature of the relationship between common mental health disorders and ecstasy use have yielded inconsistent results ([de Win et al, 2006], [Huizink et al, 2006] and [Lieb et al, 2002b]). Two small sample size studies found no relationship ([de Win et al, 2006] and [de Win et al, 2007]), whereas two larger scale longitudinal studies found that anxiety and depression preceded ecstasy use disorders in early adulthood ( [Huizink et al, 2006] and [Lieb et al, 2002b]). …”
Section: Introductionmentioning
confidence: 96%
“…84 There is evidence that even limited exposure to ecstasy can be harmful to the brain. de Win and colleagues 85 found prolonged vasoconstriction in the frontal cortex and associated increased impulsivity scores in users of a small amount of ecstasy when compared with nonusers. Sleep changes also were reported in MDMA users.…”
Section: Methamphetaminementioning
confidence: 98%
“…Recent evidence from animal and human studies indicate that specific components of executive functions, including dysfunctional impulsivity and decision-making, may predate initiation of drug use and mediate the transition between drug use and drug dependence (Belin et al, 2008;Dalley et al, 2007;Tarter et al, 2003). Accordingly, human studies have shown mild executive deficits in recreational users of cannabis and psychostimulants (De Win et al, 2007;Leland and Paulus, 2005). On the other hand, there is evidence that intensive exposure leading to dependence to different drugs, including cannabis, psychostimulants and opioids, dose-dependently impair several domains of executive functions (i.e.…”
Section: Introductionmentioning
confidence: 98%